A dilemma regarding the nature of norms - Caracciolo, Ricardo (Revus (Ljubljana), 2018)
Most philosophical theories generally accept a set of ideas concerning the nature of norms together with a certain conception of action that can be traced back to Hume. These ideas can be expressed clearly through several theses that are notoriously plausible. On the one hand, there is the thesis that norms, and the duties constituted by norms, are objective in a certain sense, while on the other hand, there is the thesis that the concept of "norm" implies the possibility of complying (or not complying) with the relevant normative requirements. The problem is that these theses cannot be held simultaneously, thus giving rise to a genuine dilemma. This paper explores several ways of avoiding the dilemma, and argues that they are all ultimately unsuccessful.
Keywords: action; desires; motivation; možnost; nagib; norme; norms; objectivity; objektivnost; possibility; ravnanje; razlogi; reasons; želje